Automatic Mixing of Bio-Samples Using Micro-Channel and Centrifugation - CAFFREY, MARTIN (IEEE, 2007)
Automatic mixing of bio-samples using micro-channel and centrifugation is considered. Existing methods for mixing bio-samples for life science applications use micro-well and micro-stirrer which are ineffective when used with highly viscous materials at the microliter or nanoliter level. Our method mixes viscous bio-samples in micro-capsules using micro-channel and centrifugation which minimizes contact with mixing tools. To introduce the method, firstly the design of the micro-capsule along with the micro-channel is presented. Secondly, a hydrodynamic model describing the flow of viscous materials in the micro-channel is presented, and the average sample velocity and the traveling time through the micro-channel are analyzed. Thirdly, the relationship between centrifugation speed and time is given to achieve effective and efficient control of the flow. Finally, experimental and theoretical results are compared.
PUBLISHED
Keywords: Medical engineering; centrifugation